2017
DOI: 10.1016/j.seizure.2016.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Why epilepsy challenges social life

Abstract: Social bonds are at the center of our daily living and are an essential determinant of our quality of life. In people with epilepsy, numerous factors can impede cognitive and affective functions necessary for smooth social interactions. Psychological and psychiatric complications are common in epilepsy and may hinder the processing of social information. In addition, neuropsychological deficits such as slowed processing speed, memory loss or attentional difficulties may interfere with enjoyable reciprocity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 36 publications
(51 reference statements)
1
53
1
4
Order By: Relevance
“…Both older age and feeling depressed are known to be associated with sexual problems in PWE. In a recent review by Steiger and Jokeit, 30 In a study by Fisher et al, 6 32% of the patients reported living with a constant fear of the next seizure; this is a lower proportion than in our sample (nearly 50%).…”
Section: Psychosocial Problemscontrasting
confidence: 65%
See 1 more Smart Citation
“…Both older age and feeling depressed are known to be associated with sexual problems in PWE. In a recent review by Steiger and Jokeit, 30 In a study by Fisher et al, 6 32% of the patients reported living with a constant fear of the next seizure; this is a lower proportion than in our sample (nearly 50%).…”
Section: Psychosocial Problemscontrasting
confidence: 65%
“…As we did not ask the patients to specify the difficulties, we may only speculate about the reasons. In a recent review by Steiger and Jokeit, 30 the authors emphasize that although social contacts have a positive effect on health, morbidity, and self-esteem and may counteract stress, PWE are also at a risk of reduced social cognitive skills and therefore may be more likely to experience communication and interpersonal difficulties. Overall, comorbid depression can be a strong barrier against many aspects of successful integration in society.…”
Section: Psychosocial Problemsmentioning
confidence: 99%
“…The software randomly selected the number of sample sites to exclude bias, ranging from 60 -110. Counts were calculated and expressed as neurons per 100 mm 3 .…”
Section: Histologymentioning
confidence: 99%
“…2 Mesial temporal lobe epilepsy (MTLE), the most common form of focal epilepsy and most common intractable seizure disorder, is characterized by spontaneous recurrent seizures and an increased risk of comorbid conditions including anxiety, depression, cognitive impairment, and sudden death. [3][4][5] Patients with MTLE are often referred for surgical resection of the seizure focus. Such surgery necessitates coordinated medical care with a multidisciplinary team that includes neurosurgeons, neurointensivists, neurologists, and neuroanesthesiologists.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, as anyone who lives with a chronic neurological or psychiatric condition knows, some of the functional differences and experiences our brains provide are less than ideal. Drugs do not control seizures in around one third of the people with epilepsy, and epilepsy that cannot be reasonably well controlled can have a devastating impact on quality of life (Laxer et al, 2014;Steiger and Jokeit, 2017). Temporal lobe epilepsy is so named because tissue in the temporal lobe of the brain does not function normally and is responsible for generating seizures.…”
Section: Plasticity and Diseasementioning
confidence: 99%